The ethnographic cinema of Jean Rouch - Miotti, Maurício (2021)
Jean Rouch developed in his film-ethnographic work a new way of making cinema and anthropology, providing possibilities for both fields. This article aims, through a study in visual anthropology, to present the ways in which the documentary films by Robert Flaherty and Dziga Vertov influenced the work of Jean Rouch, in addition to demonstrating the main characteristics and films of Jean Rouch, and the concepts developed in his works. Therefore, this work is intended to be an introduction to Rouchian ethnographic cinema, to provide a first contact with the work this anthropologist-filmmaker.